Continuous coaxial nozzle designs for improved powder focusing in direct laser metal deposition. (November 2022) - Gabor, Theodore; Yun, Huitaek; Akin, Semih; Kim, Kyung-Han; Park, Jong-Kwon; Jun, Martin Byung-Guk
Abstract: Direct Laser Metal Deposition (DLMD) is a type of Additive Manufacturing (AM) that deposits blown metallic powders from a nozzle onto a substrate. These powders are then simultaneously fused together by a high powered (0 . 1–1 kW, often ND:YAG) laser to form a deposited layer. Out of the various nozzle designs Continuous Coaxial nozzles provide the most even spray profile due to their annular profile. This is at the cost of a reduction in spray focusing. In this paper, the authors use full factorial analysis of simulated gas-powder nozzle flows to determine the impact of inlet pressure (1–10 kPa ), powder inlet angle (0° – 25°), powder inlet offset (0–10 mm offset from the centerline), and internal groove shape (no grooves, straight grooves, tapered grooves) on nozzle focusing and powder velocity. It was determined that 1 mm wide straight grooves provided the best focusing, with powder concentrations reaching from 0 . 3 to 0 . 45 kg/m 3 and particle cloud diameters reaching as low as 6 mm. CFD simulations showed that straight grooves drastically reduce tangential particle velocity components, forcing powders to point towards the nozzle's focal point. A second batch of designs with a smaller nozzle angle (from 17° to 12°) focused on examining other groove geometries, including wider straight grooves and helical grooves. These simulations confirmed that narrow, straight grooves with uniform thickness provide improved powder focusing by controlling powder exit trajectories. In addition, helical grooves with steeper helical angles reduced the powder spray divergence. Finally, one control and the two best performing designs from each batch were manufactured and tested in a lab setting to experimentally observe the overall spray profile. Both the simulations and experiments showed an improvement in nozzle focusing with the addition of straight nozzle grooves, with experimental results showing a 17–18 % decrease in the spray width compared to the control nozzle.